Circulating concentrations of biomarkers and metabolites related to Vitamin status, one-carbon and the kynurenine pathways in US, Nordic, Asian, and Australian populations - Midttun, Ø (American Society for Nutrition, 2020)
10.3945/ajcn.116.151241